Information Security and Cryptology 5th International Conference, Inscrypt 2009, Beijing, China, December 12-15, 2009. Revised Selected Papers - Bao, Feng.; Yung, Moti.; Lin, Dongdai; Jing, Jiwu.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the thoroughly refereed post-conference proceedings of the 4th International Conference on Information Security and Cryptology, Inscrypt 2009, held in Beijing, China, in December 2009. The 22 revised full papers and 10 short papers presented were carefully reviewed and selected from 147 submissions. The papers are organized in topical sections on cryptanalysis; signature and signcryption; key exchange; private computations; cipher design and analysis; public key cryptography; network and system security; hardware security; and web security.
Keywords: Computer science; Computer Communication Networks; Data protection; Data encryption (Computer science).; Computer software; Information Systems; Computer Science; Computer Communication Networks; Data Encryption; Management of Computing and Information Systems; Algorithm Analysis and Problem Complexity; Systems and Data Security; Computers and Society